Flood Modeling for the Cisanggarung River in the Cilengkrang Village using the HEC-RAS Software - Muhamad Qori Fajar; Adam Rehananda; Sulistijo Edhy Purnomo (Riviera Publishing, 2024)
This research aims to model the flood overflow of the Cisanggarung River in Cilengkrang Village using HEC-RAS software. A quantitative method was used with a focus on hydrological and hydraulic analysis. The hydrological analysis includes rainfall calculation, Thiessen Polygon method, frequency analysis, rainfall intensity, Nakayasu method, and planned discharge calculation. Hydraulic analysis was performed using HEC-RAS to model flood overflow. The research results show that the annual rainfall in the study area varies significantly, with the highest recorded rainfall of 1290 mm in 2020. The planned discharge of the Cisanggarung River was calculated at 2137 m³/second. HEC-RAS modeling revealed that the river cross-section capacity is inadequate to contain flood discharge, especially in the upper part near the settlement. Flood distribution occurs at several points along the river with varying levels of elevation. This research provides important information for flood disaster mitigation planning in the Cilengkrang Village area and its surroundings and demonstrates the effectiveness of using HEC-RAS in river flood modeling.